A new EPOR/CD131 heteroreceptor agonist EP-11-1: a neuroprotective effect in experimental traumatic brain injury - Oleg V. Antsiferov; Roman F. Cherevatenko; Mikhail V. Korokin; Vladimir V. Gureev; Anastasia V. Gureeva; Mariya A. Zatolokina; Elena V. Avdeyeva; Lyudmila A. Zhilinkova; Inga M. Kolesnik (Belgorod National Research University, 2021)
Introduction: EP-11-1 (UEHLERALNSS) is a short-chain erythropoietin derivative without have erythropoietic activity. It was created by modifying a peptide mimicking the spatial structure of the erythropoietin a-helix B pHBSP. One of the promising directions of its administration is the correction of morphofunctional disorders that occur in traumatic brain injury (TBI). Materials and methods: The study was performed in 160 male Wistar rats, weighing 180-200 g.TBI was simulated using the drop-weight method. To assess the emerging morphofunctional disorders and a degree of their correction, we used the severity of neurological deficit, indicators of locomotor activity and exploration, a marker of brain injury S100B and morphological examination. Results and discussion: The combined administration of a new EPOR/CD131 heteroreceptor agonist EP-11-1 with citicoline and trimetazidine led to a more pronounced correction of the neurological deficit when compared not only to the group of the "untreated" animals, but also to the groups of animals to which these drugs had been administered as monotherapy (p < 0.05). The same tendency was also observed in the study of locomotor activity and exploration. A biochemical study showed that the administration of all three combinations led to a statistically significant (p < 0.05) decrease in the S-100B concentration compared not only to the group of "untreated" animals, but also to the groups of animals to which these drugs had been administered as a monotherapy. Conclusion: The results of the conducted experiments prove the most pronounced positive dynamics in the combined administration of the new EPOR/CD131 heteroreceptor agonist EP-11-1with citicoline and trimetazidine.